Voluntary Resistance Running as a Model to Induce mTOR Activation in Mouse Skeletal Muscle - D’Hulst, Gommaar; Palmer, Andrew S.; Masschelein, Evi; Bar-Nur, Ori; De Bock, Katrien (Frontiers in Physiology, 2019)
Long-term voluntary resistance running has been shown to be a valid model to induce muscle growth in rodents. Moreover, the mammalian target of rapamycin complex 1 (mTORC1) is a key signaling complex regulating exercise/nutrient-induced alterations in muscle protein synthesis. How acute resistance running affects mTORC1 signaling in muscle and if resistance applied to the wheel can modulate mTORC1 activation has not yet been fully elucidated. Here we show that both acute resistance running and acute free running activated mTORC1 signaling in the m. gastrocnemius, m. soleus, and m. plantaris, but not in m. tibialis anterior of mice when compared to sedentary controls. Furthermore, only the low threshold oxidative part in the m. gastrocnemius showed increased mTORC1 signaling upon running and acute heavy-load resistance running evoked higher downstream mTORC1 signaling in both m. soleus and m. plantaris than free running without resistance, pointing towards mechanical load as an important independent regulator of mTORC1. To conclude, in this study we show that voluntary resistance running is an easy-to-use, time-efficient and low stress model to study acute alterations in mTORC1 signaling upon high-load muscular contractions in mice.